Analisis Faktor Kepatuhan Lansia dalam Pemanfaatan Pelayanan Posyandu Lansia di Banjar Wangaya Kaja Denpasar Utara - Ni Kadek Muliawati; Nurul Faidah (Universitas Baiturrahim, 2021)
There are 901 million people aged 60 years or over, comprising 12% of the world's population (Department of Economic and Social Affairs, 2015). The Morbidity rate in the elderly in 2015 was 28.62%, which means that for every 100 elderly people, 28 people are sick (Kemenkes RI, 2017). The utilization of health services in the elderly Posyandu is still far from the expected target. (Aprilia, 2019): out of 105 elderly, 65.7% do not regularly go to Posyandu in Pekanbaru. The data on elderly visits to the Banjar WangayaKaja elderly posyandu in the last three months were 41 elderly (29.31%). This study aims to analyze the obedience factor of the elderly in the utilization of posyandu services for the elderly.A cross-sectional study was conducted in Banjar WangayaKaja, Denpasar Utara in October-November 2019. The sample was 99 elderly with non-probability sampling technique, namely purposive sampling. Elderly who changed residence, were sick / hospitalized and totally dependent were not sampled. Demographic data, the distance from the elderly's house to the elderly posyandu and the knowledge of the elderly were obtained by distributing questionnaires, the attendance of the elderly was obtained based on attendance in the past one year. Multivariate analysis with logistic regression was carried out to obtain POR.There was a relationship between POR age = 0.17 (95% CI: 0.03-0.94), education POR = 2.71 (95% CI: 1.23-6.01) and the role of cadres POR = 59 , 64 (95% CI: 9,18-387,41) with elderly compliance in the utilization of posyandu services for the elderly. Factors that were not statistically found to be associated were gender (p-value: 0.552), occupation (p-value: 0.490), location distance to elderly posyandu (p-value: 0.009) and knowledge (p-value: 0.894). Cadres further enhance their roles, such as conducting home visits, as motivators as an effort to improve posyandu services for the elderly.